ASSESSMENT OF THE BORDER ARGUN RIVER WATER QUALITY FROM THE ECOLOGICAL POINT OF VIEW - Valery N. Zaslonovskiy; Maksim A. Bosov; Natalya K. Raenko (Водное хозяйство России: проблемы, технологии, управление)
Based on archival materials and expedition observation data, the water quality of the border Argun River is assessed. The characteristic pollutantsaredetermined. The linear trends of changes in the concentrations of these pollutants for 2016 – 2019 are analyzed, showing changes in concentrations on the border section of the river more than five hundred and fifty kilometers long from its exit from the territory of a neighboring state. The basic indicators of anthropogenic load (PAN6) were calculated for the observation stations, the trends in their changes were considered, and with this in mind, the ecological well-being of the water body in this section was assessed.